PENGARUH KOMPENSASI, PELATIHAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA DENPASAR BARAT - Reggina, Viere Ekadewi; Sintaasih, Desak Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Human resources are valuable assets owned by the company. Optimal performance can be achieved through compensation, training, and motivation. The West Denpasar Tax Service Office is an office that provides tax services to the public. At this location, there are still problems related to employee performance through attendance data and preliminary studies. The purpose of this study was to determine the effect of compensation, training, and motivation on employee performance. The research location is the West Denpasar Tax Service Office. The number of employees includes in the population is 97 people. The number of samples in this research was 97 people which was determined by the saturated sampling technique. Data collection using interviews and questionnaires. Data analysis was performed using SPSS version 24. The results showed that the performance of the employees of the West Denpasar Pratama Tax Service Office could increase due to good compensation and training and high motivation. Compensation, training and motivation have a positive and significant effect on the performance of West Denpasar KPP Pratama employees. Motivation is the variable that most influences employee performance